Night blindness and conjunctival xerosis caused by vitamin A deficiency in patients with cystic fibrosis. Issue 8 (August 1989) - Rayner, R J; Tyrrell, J C; Hiller, E J; Marenah, C; Neugebauer, M A; Vernon, S A; Brimlow, G
Abstract : Forty three patients with cystic fibrosis, aged 8-44 years (median 16 years), were examined for evidence of vitamin A deficiency. Eight patients had abnormal dark adaptation tests and three had conjunctival xerosis. Serum vitamin A and retinol binding protein concentrations were significantly lower in the affected patients who were also more likely to have abnormal liver function tests. Five patients were treated with 100, 000-200, 000 IU water miscible vitamin A orally and their daily vitamin supplements were increased to maintain normal concentrations. In four patients dark adaptation tests were repeated. Three were normal, but one patient required three further doses of water miscible vitamin A and a daily supplement of 12, 000 IU vitamin A before her dark adaptation threshold returned to normal. Adolescents with cystic fibrosis are liable to develop night blindness and conjunctival xerosis, particularly if they have liver disease or fail to take daily vitamin supplements.